Development of crawler steering gearbox for combine harvester straight forward and steering in situ - Tang, Zhong; Zhang, Haotian; Li, Hongchang; Li, Yaoming; Ding, Zhao; Chen, Jinsong (International Journal of Agricultural and Biological Engineering, 2020)
Soil compaction and accumulation are caused by crawler steering. Soil characteristics would affect the ability of crawler straight forward and steering in situ. This paper studied the principle of straight forward steering and steering in situ mode of traditional unilateral brake steering gearbox of a crawler combine harvester. Then a positive and negative steering gearbox model was developed and processed. The performance of positive and negative steering gearbox was analyzed by performing two steering modes on soil compaction effect. Results showed that the positive and negative steering gearboxes can achieve three operating modes, such as straight forward, unilateral brake steering, and positive and negative steering in situ. The positive and negative steering in situ was smooth and without soil accumulation phenomenon. When the crawlers center distance, crawler grounding length, crawler width were 1150 mm, 1620 mm and 450 mm respectively, the rolling area and the scratch free area of positive and negative steering gearbox were 5.37 m2 and 0.36 m2 respectively. However, the rolling area and the scratch free area produced by unilateral brake steering gearbox were 13.92 m2 and 1.88 m2 respectively, which was 8.55 m2 larger than that of positive and negative steering gearbox. The crawler with positive and negative steering gearbox has minor damage to paddy soil. This research can provide a theoretical basis for the smooth steering in situ and structural optimization of the crawler steering gearbox. Keywords: steering gearbox, rolling soil track, steering in situ, rolling and scraping, shaft and gear DOI: 10.25165/j.ijabe.20201301.3957 Citation: Tang Z, Zhang H T, Li H C, Li Y M, Ding Z, Chen J S. Developments of crawler steering gearbox for combine harvester straight forward and steering in situ. Int J Agric & Biol Eng, 2020; 13(1): 120–126.